STUDI SHARED LEADERSHIP DAN PERANNYA DALAM MENINGKATKAN KINERJA KARYAWAN - Fitri Wulandari; Oktaviyana Ayu Putriyanti (University of Merdeka Malang, 2020)
This paper aims to analyze the effect of shared leadership on employee performance with organizational commitment and employee creativity as a mediating variable. This study uses a population of all employees of PT. Pos Indonesia Solo area, with a total sample of 130 respondents. The sampling technique uses random sampling. Data were analyzed using path analysis with SPSS version 23. The results showed that shared leadership had a positive and significant effect on employee performance. The results also show that shared leadership has a positive and significant effect on organizational commitment and also on employee creativity. Organizational commitment and work creativity also show as a good antecedent in improving employee performance. The results of this study have proven that organizational commitment and employee creativity can mediate the influence of shared leadership on employee performance